Inmigración asiática y homoerotismo: nuevas configuraciones de la otredad en el teatro argentino actual - Beatriz Trastoy (Les Cahiers ALHIM)
Argentine theatre during the first decades of 20th century staged the cultural and linguistic misunderstandings that European immigration caused in local way of life. The recent Asian immigration established in Buenos Aires since the 70’ brings forth new ethic and aesthetic issues in plays which deal with the question of otherness in a wide sense. As an example, this article analyzes Shangay (2004) by José María Muscari, which stages with a critical sight the social and racial prejudices of Argentine middle class by means of the analogy between Far East culture (or what is usually taken by such) and homoerotism. The sainete-genre (deeply rooted in the Argentine theatrical tradition) is thus re-interpreted by means of parodical procedures. Kitsch, snobbery and frivolity, which confuse everything, and also prejudices, intolerance and discrimination, that stigmatize everything, are the pathetic background of a homosexual love story that leaves traditional gender constructions far behind.